Sensitive Detection of KRAS Mutations Using Enhanced-ice-COLD-PCR Mutation Enrichment and Direct Sequence Identification - How Kit, Alexandre; Mazaleyrat, Nicolas; Daunay, Antoine; Nielsen, Helene Myrtue; Terris, Benoît; Tost, Jörg (Human mutation, 2013)
ABSTRACT A number of methods allowing the detection of low levels of KRAS mutations have been developed in the last years. However, although these methods have become increasingly sensitive, they can rarely identify the mutated base directly without prior knowledge on the mutated base and are often incompatible with a sequencing‐based read‐out desirable in clinical practice. Here, we present a modified version of the ice‐COLD‐PCR assay called Enhanced‐ice‐COLD‐PCR (E‐ice‐COLD‐PCR) for KRAS mutation detection and identification, which allows the enrichment of the six most frequent KRAS mutations. The method is based on a nonextendable chemically modified blocker sequence, complementary to the wild‐type (WT) sequence leading to the enrichment of mutated sequences. This assay permits the reliable detection of down to 0.1% mutated sequences in a WT background. A single genotyping assay of the amplification product by pyrosequencing directly following the E‐ice‐COLD‐PCR is performed to identify the mutated base. This developed two‐step method is rapid and cost‐effective, and requires only a small amount of starting material permitting the sensitive detection and sequence identification of KRAS mutations within 3 hr. This method is applied in the current study to clinical colorectal cancer samples and enables detection of mutations in samples, which appear as WT using standard detection technologies. Enhanced‐ice‐COLD‐PCR allows the enrichment, detection, and sequence‐based identification of the six most frequent KRAS mutations. The method is based on a non‐extendable LNA blocker sequence, complementary to the wild type sequence leading to the enrichment of mutated sequences and permitting the reliable detection of 0.1 % mutated sequences. A single genotyping assay directly following Enhanced‐ice‐COLD‐PCR identifies the mutated base. This developed method is rapid and cost‐effective and enables the detection and sequence identification of KRAS mutations within three hours.